Impact of Mining on the Floral Diversity: A Case Study from the Rajrappa Coal Mining Area of Jharkhand, India - Kumar, Sanjeev; Barman, Tanay; Raj, Hans; Kumar, Ankit; Ranjan, Rajeev; Kumar, Arvind (Indian Forester, 2024)
The global challenge of safeguarding biodiversity is intensified by mining activities, necessitating prompt action from policymakers. Mining disrupts forest biodiversity, ecosystem services, and landscapes, making It difficult for species to thrive and regenerate. Although coal mining Is a source of government revenue, it results in extensive deforestation and soil degradation. The present investigation was carried out In the Rajrappa coal mining area in Ramgarh district of Jharkhand state. The floral survey was carried out by stratified random sampling. Five buffer zones were created at a distance of 1 km from the center of the mining area. Collected data were analyzed for density, richness. Total 132 anglosperm species (Trees: 39; Shrubs: 51 and Herbs: 42) were reported from 67 families and 42 genera from the study area. Species richness and total density was very low near the center of the mine while increases when It goes away from the mining area. Richness o f the species was ranged from 9-16. Density of trees and shrubs were ranged from 440-760 and 750-1200 Ind/ha. Total basal area was ranged from 65.81-80.16 m2ha-1. Density of herbs was ranged from 16-27 Ind/m2. The contagious dispersion tendency of species throughout the mining region suggests that natural vegetation degradation Is Increasing as a result of mining. The phytosociologicai Indices demonstrate the Impact in the forest structure and dynamics of the region. The study concludes that the subsequent analysis of ecological status and give the policymakers to formulate proper restoration plan and management practices to safeguard the forest biodiversity.